Heavy metal concentrations in the bivalve Corbicula fluminalis shells from Shatt Al-Arab River - Al-Jaberi, M.H. (Mesopotamian Journal of Marine Sciences, 2022)
This study was to investigate the contamination in the Shatt Al-Arab River by determining the heavy metals in the limnic bivalve Corbicula fluminalis, a sentinel species. The results showed that the values of Ba, Zn, Pb, Ni, Co, Cr, Sr, Cu, Mn and Fe in Corbicula fluminalis shells increased significantly from the beginning point toward the central part of Shatt Al-Arab River. This increase may be explained from the high incidence of pollution from sewage, development, and industry in the central part of Shatt Al-Arab River compared to the north